2018
DOI: 10.2478/mme-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Welding Parameters and Microstructure and Fracture Mode Characterization of GMA Welding by Using Taguchi Method on SS304H Austenitic Steel

Abstract: This study is centre on optimizing different welding parameters which affect the weldability of SS304H, Taguchi technique was employed to optimize the welding parameters and fracture mode characterization was studied. A number of experiments have been conducted. L9 orthogonal array (3×3) applied for it. Analysis of variance (ANOVA) and signal to noise ratio (SNR), a statistical technique was applied to determine the effect of different welding parameters such as welding current, wire feed speed and gas flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The welding parameters were selected by reviewing different previous researches that were conducted on stainless steel materials using TIG welding. The analysis of variance (ANOVA) was used to determine which parameters had substantial impacts on responses [29]. In this paper, the most important process parameters of TIG welding that significantly enhanced the study's responses and were frequently employed for stainless steel materials were examined and identified.…”
Section: Selections Of Parameters and Orthogonal Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…The welding parameters were selected by reviewing different previous researches that were conducted on stainless steel materials using TIG welding. The analysis of variance (ANOVA) was used to determine which parameters had substantial impacts on responses [29]. In this paper, the most important process parameters of TIG welding that significantly enhanced the study's responses and were frequently employed for stainless steel materials were examined and identified.…”
Section: Selections Of Parameters and Orthogonal Arraymentioning
confidence: 99%
“…Because of the differences in scope and scale, the original data or S/N ratios in a data series must be normalized to produce a similar sequence. In this case, the S/ N ratios of hardness, ultimate tensile strength, and bending strength were preprocessed using the higher is the better normalization formula shown on equation (3) [33].…”
Section: Normalization Of Datamentioning
confidence: 99%
“…With the welding current from 160 to 240 A, the hardness of the weld area appears to decrease significantly. By using Taguchi techniques to improve welding parameters and fractures, [2] Rizvi and Ali (2018) were able to improve various welding parameters that affect the weldability of SS304H. The orthogonal array L9 is employed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors noticed superior hardness values at higher welding speed and mean current. In another work related to MIG welding of SS 304 H, Rizvi et al 7 identified that gas flow rate is the most influential factor on the mechanical properties, followed by arc voltage and wire feed speed. Few authors explored the joining of SS 304 with filler materials and analysed the property variation with different filler materials.…”
Section: Introductionmentioning
confidence: 99%